Studies of silver species for low-temperature CO oxidation on Ag/SiO2 catalysts - Zhang, X.; Qu, Z.; Li, Xin Yong; Wen, M.; Quan, X.; Ma, D.; Wu, J. (Pergamon Press, 2010)
The active species and particle size of silver catalysts for CO oxidation were discussed in this paper by investigating the effects of Ag loading and different pretreatments on the crystallite structure of silver catalysts. It was found that 8 wt% Ag/SiO2 catalyst pretreated with O2 at 500 °C exhibited high catalytic performance (T98 = 65 °C).When the catalyst further treated with H2 at 200 °C following O2 treatment, a better catalytic performance (T98 = 50 °C) was obtained. However, it was decreased with the increase the reduction temperature to 300 °C. Crystallite Ag and Ag2O species were observed after O2 pretreatment at 500 °C. Subsequent H2 treatment at low temperatures (50-200 °C) caused the reduction of Ag2O species, the formation of Agnd+ clusters and the high dispersion of crystallite silver. Reduction at high temperature (>200 °C) resulted in decreased amount of the oxygen species and the aggregation of metallic silver particles, which were confirmed by the disappearance of the Agnd+ clusters and the sharpening of the band centered at 410 nm. Therefore, oxygen-containing Ag species might be proposed as the active species and silver particle size of ca. 4.5-5.5 nm would be favorable for the low-temperature CO oxidation. © 2010 Elsevier B.V. All rights reserved.